Teaching strategies: promoting the development of moral competence in undergraduate students - Cleci de Fátima Enderle; Rosemary Silva da Silveira; Graziele de Lima Dalmolin; Valéria Lerch Lunardi; Liziane Iturriet Avila; Carmen Carballo Dominguez (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To identify strategies and spaces used by professors to promote the development of the moral competence of nursing undergraduate students. Method: Qualitative research, developed with 20 nursing professors, through a semi-structured interview, from July to October 2016. Data were submitted to discursive textual analysis. Results: Three categories were constructed: Active methodologies as strategies for the development of moral competence; Knowledge and development of clinical reasoning as motivating spaces of moral competence; Attitude of professors as a strategy for dialogue, empathy, recovery of moral values and development of caring skills. Final considerations: The use of strategies and spaces to develop pedagogical actions favors the search for knowledge, clinical reasoning and the approach of ethical and moral aspects that collaborate for the development of the moral competence of nursing undergraduate students.